Influence of steel surface composition on ZDDP tribofilm growth using Ion implantation - Ueda,M; Kadiric,A; Spikes,H (Tribology Letters, 2021)
This paper examines the influence of steel surface composition on antiwear tribofilm formation by ion-implanting typical steel alloying elements, Ni, Mo, Cr, V and W, into AISI 52100 bearing steel surfaces. Such implantation changes the chemical composition of the steel surface but has relatively little effect on its mechanical properties or topography. The behaviour of zinc dialkyldithiophosphate (ZDDP) antiwear additive was studied. The study employs a ball on disc tribometer with ability to monitor tribofilm development and a range of analytical tools including STEM-EDX, XPS and FIB-TEM to analyse the formed tribofilms. It was found that Ni implantation promotes ZDDP tribofilm formation while Mo and Cr implantation deters tribofilm growth. V and W implantation do not significantly change tribofilm formation. Results on the influence of ZDDP concentration on tribofilm formation rate with different implanted metals suggest that one important mechanism by which steel composition influences tribofilm formation may be by controlling the extent of ZDDP adsorption. This study shows the importance of steel surface composition on ZDDP response and also demonstrates a powerful way to study and potentially improve the tribological performance of machine components via a combination of lubricant formulation and surface modification.